Analysis of the effect of financial ratios on ROA at Commercial Banks on the IDX - Murtiningrum, Widiastuti; Wahyuningsih, Erna (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Financial system resilience, especially indonesia's current banking condition amid the crisis and global economic pressures, has been maintained and there has been an increase in intermediation, as can be seen from the high capital adequacy ratio (CAR), the ratio of operating expenses to operating income increased during the Covid pandemic, the ratio of non-performing loans (NPL), net interest income (NIM) increased in line with improving macro conditions, with the high capital owned there is an increase in the fulfillment of loan demand (LDR) with a low ratio level, profitability ratio (ROA) that is increasing by utilizing assets and capital (equity) to the maximum extent that is maintained. Judging from the existing conditions, this study was conducted with the aim of analyzing, testing and concluding the influence of CAR, BOPO, NPL, NIM and LDR on ROA in 4 state-owned banks listed on the Indonesia Stock Exchange for the 2017-2022 period using secondary data through financial statement information of Commercial Banks. Quantitative analysis techniques with multiple linear regression as well as classical assumption tests using Eviews 9. The results show that BOPO, NIM and LDR partially have a positive and significant influence, while CAR and NPL have no significant influence on ROA Simultaneously CAR, BOPO, NPL, NIM and LDR affect the increase or decrease in ROA. From independent variables to dependent variables have a predictive ability of 98% and 2% are influenced by other variables outside the study.